Investigation of the drug release modifying property of Pentadesma butyracea gum in diclofenac sodium matrix tablets - Mary-Ann Archer; Kwabena Ofori-Kwakye; Raphael Johnson; Isaac Yaw Attah; Frederick William Akuffo Owusu; Prince George Jnr Acquah; Samuel Lugrie Kipo (PLoS ONE, 2026)
Background Natural gums have long served as essential excipients in pharmaceutical formulations, traditionally functioning as binders, disintegrants, suspending agents, and emulsifiers. Their role has expanded to include drug delivery carriers in advanced systems such as matrix formulations, gene therapy, and nanomedicine. Increasing attention has been given to natural gums over synthetic alternatives due to their non-toxicity, biodegradability, affordability, and availability. This study investigated the potential of Pentadesma butyracea gum as a matrix-forming agent for the extended release of diclofenac sodium. Methods The crude gum was harvested from the stem bark of Pentadesma butyracea and purified using ethanol precipitation. Fourier-transform infrared spectroscopy (FTIR) was employed to assess potential interactions between the gum, diclofenac sodium, and other excipients. Matrix tablets (PM01–PM05) containing varying concentrations (15–35% w / w ) of the purified gum were prepared via wet granulation, along with a control batch (PM06) lacking the gum. Additionally, the PM01 formulation was optimised by incorporating xanthan gum at concentrations of 10–20% w / w (PM01A–PM01C). All formulations were assessed for weight and dimensional uniformity, mechanical integrity, drug content, and in vitro release characteristics. Comparative dissolution profiles were assessed against an innovator brand using the similarity (f₂) and difference (f₁) factors. Drug release kinetics and mechanisms were analysed using appropriate mathematical models. Results All batches passed the uniformity of weight and dimensions tests, drug content (99.11–101.87%), friability (0.25–0.79%), hardness (7.74–8.83 Kgf), and tensile strength (1.29–1.49 MPa). The control batch (PM06) failed to meet dissolution criteria, releasing only 60.46% of diclofenac sodium within 45 minutes. In contrast, formulations containing P. butyracea gum exhibited a gradual, concentration-dependent, time-mediated release, with all test batches (PM01–PM05) releasing over 50% of the drug within 45 minutes. Among the optimised formulations, PM01C exhibited a modified release profile, with 19.90 ± 0.508% of the drug released at 2 hours and 100.26 ± 2.118% at 24 hours, consistent with the British Pharmacopoeia standards. The release profile of PM01C was comparable to the reference product (f₂ = 79.35; f₁ = 2.93) and followed zero-order kinetics. PM01A and PM01B exhibited Korsmeyer-Peppas release kinetics. Mechanistically, drug release occurred via non-Fickian diffusion for PM01C and Fickian diffusion for PM01A and PM01B. Conclusion A matrix system comprising 15% w / w P. butyracea gum and ≥ 20% w / w xanthan gum effectively extended the release of diclofenac sodium over 24 hours, demonstrating its potential application in extended-release formulations.